2015
DOI: 10.1097/qad.0000000000000902
|View full text |Cite
|
Sign up to set email alerts
|

Reduced ovarian reserve relates to monocyte activation and subclinical coronary atherosclerotic plaque in women with HIV

Abstract: Objective(s) To investigate differences in subclinical coronary atherosclerotic plaque and markers of immune activation among HIV-infected and non-HIV-infected women categorized by degree of ovarian reserve and menopause status. Design Cross-sectional evaluation. Methods Seventy-four women (49 HIV-infected, 25 non-HIV-infected) without known CVD were classified as premenopausal, premenopausal with reduced ovarian reserve, or postmenopausal based on menstrual history and antimullerian hormone (AMH) levels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 37 publications
2
38
0
Order By: Relevance
“…26 A cross-sectional evaluation of both healthy and HIV-infected women concurred that premenopausal women with undetectable AMH levels had larger atherosclerotic plaques than premenopausal women with detectable AMH levels. 27 Although these observations could potentially be explained by a relationship between either ovarian reserve status or AMH levels and lipid measures, 18,[28][29][30] the results of the current study add to evidence suggesting that the association of AMH with CVD occurrence is independent from cholesterol levels. 26,27 It is interesting to note that a previous study did not find any association between age-specific AMH levels and silent coronary artery disease, based on a composite factor of various electrocardiography-based ischemic changes, in a 10-year follow-up period.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…26 A cross-sectional evaluation of both healthy and HIV-infected women concurred that premenopausal women with undetectable AMH levels had larger atherosclerotic plaques than premenopausal women with detectable AMH levels. 27 Although these observations could potentially be explained by a relationship between either ovarian reserve status or AMH levels and lipid measures, 18,[28][29][30] the results of the current study add to evidence suggesting that the association of AMH with CVD occurrence is independent from cholesterol levels. 26,27 It is interesting to note that a previous study did not find any association between age-specific AMH levels and silent coronary artery disease, based on a composite factor of various electrocardiography-based ischemic changes, in a 10-year follow-up period.…”
Section: Discussionmentioning
confidence: 59%
“…27 Although these observations could potentially be explained by a relationship between either ovarian reserve status or AMH levels and lipid measures, 18,[28][29][30] the results of the current study add to evidence suggesting that the association of AMH with CVD occurrence is independent from cholesterol levels. 26,27 It is interesting to note that a previous study did not find any association between age-specific AMH levels and silent coronary artery disease, based on a composite factor of various electrocardiography-based ischemic changes, in a 10-year follow-up period. 31 The high reported rate of silent coronary artery disease in this population (14%, compared to 4.8% 32 and 3.6/10000 person-years 33 in a Dutch population) suggests that the used classification of silent coronary artery disease may not be entirely able to distinguish the women with clinically relevant coronary-based ischemia from this population.…”
Section: Discussionmentioning
confidence: 59%
“…This findings implies that WLHIV with reduced ovarian reserve who still undergo menstrual cycling should not necessarily be considered to harbor low CVD risk. In this study, among WLHIV, markers of systemic immune activation were also noted to increase across progressive categories of reproductive aging(66). …”
Section: Sex-specific Mechanisms Underlying Heightened Cvd Risk Amongmentioning
confidence: 57%
“…Looby et al demonstrated that among WLHIV, reproductive aging is associated with heightened systemic immune activation(79). A series of seminal studies from the WIHS cohort have shown that WLHIV (vs. women without HIV) may experience accelerated reproductive aging.…”
Section: Heightened Systemic Immune Activation/inflammation Among Wlhivmentioning
confidence: 99%